THE INFLUENCE OF PROBIOTIC SUPPLEMENTATION OF Saccharomyces spp. Gb9 ON RATIONS TO THE WEIGHT AND PERCENTAGE OF SLAUGHTER AND CARCASS BROILER - I P. F., Cahyana; Bidura, I G. N. G.; Sumardani, N. L. G. (Jurnal Peternakan Tropika, 2017)
The study was carried out to evaluation the effect supplementation of Saccharomyces spp Gb9 isolated from chickens colon in the ration on slaughter and carcass weight, and carcass percentage broiler chickens for 6 weeks at Dajan Peken, Tabanan, Bali. The randomized complete design (RAL) with three treatments and six replicates were used in a the research. Those treatments were ration without supplementation of Saccharomyces spp Gb9 (A), ration with supplementation of 0,20% Saccharomyces spp. Gb9 (B), and ration with supplementation 0,40% Saccharomyces spp. Gb9 (C). The variables observed were slaughter, carcass weight, and carcass percentage. The study showed that treatment B and C significantly (P<0,05) increased slaughter and carcass weight and also carcass percentage than treatment A. it can be concluded that supplementation 0,20 and 0,40% of Saccharomyces spp. Gb9 on the ration can increase slaughter and carcass weight, and carcass percentage of 2-6 weeks broiler chicken. Keywords: probiotic, Saccharomyces spp. Gb9, carcass, broiler